2014
DOI: 10.3201/eid2004.131746
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against MERS Coronavirus in Dromedary Camels, United Arab Emirates, 2003 and 2013

Abstract: Camels were infected with this virus >10 years before the first human cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
231
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(258 citation statements)
references
References 33 publications
19
231
3
5
Order By: Relevance
“…Results were expressed as relative mean fluorescent intensity (RFU) for each set of quadruplicate spots of antigen, with a cutoff of 4,000 RFU as used by Meyer et al (6). Human CoV OC43 S1 was used as a proxy for bovine coronavirus (BCoV), the latter of which is known to circulate commonly in dromedaries (7,12).…”
Section: The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Results were expressed as relative mean fluorescent intensity (RFU) for each set of quadruplicate spots of antigen, with a cutoff of 4,000 RFU as used by Meyer et al (6). Human CoV OC43 S1 was used as a proxy for bovine coronavirus (BCoV), the latter of which is known to circulate commonly in dromedaries (7,12).…”
Section: The Studymentioning
confidence: 99%
“…The serum samples were tested for the presence of IgG antibodies reactive with S1 antigens against MERS-CoV (residues 1-747), severe acute respiratory syndrome CoV (residues 1-676), and human CoV OC43 (residues 1-760) by using extensively validated protein-microarray technology, as described (2,3,6,11). Results were expressed as relative mean fluorescent intensity (RFU) for each set of quadruplicate spots of antigen, with a cutoff of 4,000 RFU as used by Meyer et al (6).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of an outbreak of MERS-CoV infection in humans in Qatar in October 2013 found that dromedary camels and humans were infected with a nearly identical strain of MERS-CoV (18). Further studies from Saudi Arabia supported the hypothesis that dromedary camels act as reservoirs of MERS-CoV (17,19). Widespread circulation of different genetic variants of MERS-CoV has been found in camels and the presence of MERS-CoV specific antibodies in samples taken from camels, years earlier.…”
Section: Sources Of Infection and Transmission Routesmentioning
confidence: 82%
“…There is growing evidences that the dromedary camel is host species for MERS-CoV and plays an important role in the transmission of the viruses to human (15)(16)(17)(18)(19)(20). In August 2013, for the first time, dromedary camels were implicated as a possible source of virus causing human infection because of the presences of MERS-CoV specific neutralizing antibodies in dromedary camels from Oman and other countries in the Arabian Peninsula and North Africa (15)(16)(17)(18)(19). An analysis of an outbreak of MERS-CoV infection in humans in Qatar in October 2013 found that dromedary camels and humans were infected with a nearly identical strain of MERS-CoV (18).…”
Section: Sources Of Infection and Transmission Routesmentioning
confidence: 99%